Pediatric colchicine poisoning with survival after a “lethal” overdose: a case report - Wiem Barbaria; Ichrak Khamassi; Mohamed Fkili (Toxicology Communications, 2023)
AbstractColchicine is a tricyclic alkaloid that has both medicinal and poisonous properties. Colchicine poisoning is a life-threatening condition with high mortality.A 13-year-old girl presented to our department with vomiting, abdominal pain, and fever. She appeared generally ill with hypotension. Laboratory tests revealed thrombocytopenia, hyponatremia, acute kidney injury, elevated INR, markedly elevated troponin concentration (6721 pg/L), and elevated C-reactive protein (337 mg/L). Differential diagnoses were septic shock or pediatric inflammatory multisystem syndrome. She received hemodynamic support, empiric antibiotics, intravenous immunoglobulin, methylprednisolone, acetylsalicylic acid, and vitamin K. Her condition worsened, and she developed visual and auditory hallucinations on day 5. We then suspected drug intoxication, particularly with colchicine, which her mother took for Behçet’s disease. Blood testing revealed a high colchicine concentration, and the patient admitted to ingesting 40 tablets of colchicine in a suicide attempt. She developed frontal alopecia on day 10. She was discharged on day 17 with psychiatric follow-up.Despite the initial delayed diagnosis of colchicine poisoning, supportive treatment with corticosteroids and immunoglobulin may have saved the adolescent. Future research may determine whether either of these is effective in treatment of severe colchicine intoxication.